Implementing Holistic Criticism Model Based On Multicultural Approach In Art Appreciation Subject - ., Iriaji (KnE Social Sciences, 2017)
The practices in our teaching and learning setting suggests that art appreciation subject at school does not emphasize on exploring visual art forms and relevant critics on them as most teachers only present information about the artwork. Such teaching and learning activity cannot effectively improve students’ understanding, awareness, and sensitivity towards the cultural diversity that Indonesia owns. In response to this issue, the researcher conducts a research and development study to apply holistic criticism model in teaching art appreciation. The research begins with a preliminary study as a need and content analysis that consists of several stages: (1) identifying the difficulties that teachers face in developing art appreciation subject, (2) exploring relevant references, expert’s testimony, and FGD followed by a collaborative work with teachers in the field to decide the conceptual structure to implement holistic criticism model based on multicultural approach in art appreciation. The results show that: (1) the level of difficulty or the problems that hinder the teachers to develop and implement art appreciation subject is quite complex, (2) as an output of the study, the researcher produces a guidebook, a student book, and a worksheet that contain the conceptual structure of holistic criticism model based on multicultural approach. Keywords: holistic approach, multicultural, art appreciation.